Selected economic geography concepts for the elementary school - Fernandez, Helen Yulo 1946- (s.n.], 1974)
There is a great and growing need to put emphasis on Economic Geography in the teaching of an integrated course in the field of Social Studies as evidenced by the relevance and importance that Economic Geography has in the lives of everyone. To do this, materials to guide the Social Studies teacher are needed. But since the very few materials available are mainly for the use in the college level, and hence, not suited to the needs, language, and levels of understanding of grade school children, this paper presented only a selection of economic geography concepts applicable to the elementary grades. The selection was simplified in relation to the 1971 BPS graduated and substantive Social Studies concepts. It was the purpose of this paper to present other related ideas and explanatory notes for each concept and generalization selected and some teaching units and lesson plans to guide the teachers in developing a concept or generalization in Economic Geography.